Human-wildlife conflict along the edge of the Sundarbans mangrove forest in Satkhira, Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2022)
This paper describes the scenario of human-wildlife conflict along the edge of the Sundarbans mangrove forest in Satkhira, Bangladesh. In and around the Sundarbans mangrove forest human-wildlife conflict occurs in the category of crop and material damage, depredation of domestic animal, human laceration and human death. The animals that were mostly involved in human-wildlife conflict are tiger, crocodile, snake and monitor lizard. Due to humanwildlife conflict, a total of 172 people and 10 tigers died during the period 1990-2018. Among the total claimed human death, 97.6% (n=168) of victims were killed by tiger, 1.7% (n=3) by crocodile and 0.6% (n=1) by snake. On the other hand, among the killed tigers, the higher proportion (80%, n=8) was male and the lower proportion (20%, n=2) was female. Most of the victims (90%) were assaulted by tigers during hours of sunlight, mainly from 10:00 am to 12:00 pm (40%) and 7:00 am to 9:00 am (25%). The generation approaching middle age (age 45-59) were most commonly assaulted (33%), but the attack was also high in 30-44 age class (26%). The attacks on different professional classes comprise honey gatherers (60%), woodcutters (22%) and fishermen (18%). Tiger attacks mostly took place in Gabura (59%, n=98), Koikhali (21%, n=35), Ramjannagar (10%, n=18), Munshiganj (7%, n=11) and others places (3%, n=6). Rested on the evidence of killed (97.6%, n=168) and wounded (78%, n=247) humans by tigers, 60% of the killed people were partially consumed while 30 % were not consumed when the bodies of victims were recovered. Departed bodies were found to have been dragged a distance of 300-800 m inside the deep forest from the initial spot of attack. Human wildlife conflict hampers the animal conservation initiatives in the natural ecosystems and poses the most serious challenges to the persistence and survival of wildlife. Therefore, there is an urgent necessity to develop a conducive environment for all concerned stakeholders to rectify the situation, and to revive their capacities in the most productive and successful way.Jahangirnagar University J. Biol. Sci. 10(1 & 2): 59-70, 2021 (June & December)